Merubah Paradigma Berpikir untuk Menciptakan Ekonomi Kreatif: Pengabdian kepada Masyarakat Desa Horisan Ranggitgit Tapanuli Utara - Tiur Imeldawati; Damayanti Nababan; Goklas J. Manalu; Warseto Freddy Sihombing; Melina Agustina Sipahutar; Regina BM Nainggolan; Agnes Novianti Permata Sari; Lisdiu Tumanggor; Arifin Hutabarat (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Community service activities are part of the implementation of the Tri Dharma of Higher Education, aiming to make a real contribution to society. The Religious Extension Education Study Program at IAKN Tarutung participated in the implementation of the Tri Dharma, selecting a location in Horison Ranggitgit Village, Parmonangan District. This activity was motivated by the community's continued reliance on traditional agriculture and the lack of innovative local potential utilization. The purpose of this activity was to support government and IAKN Tarutung programs in implementing the Tri Dharma of Higher Education, as well as to encourage the community to recognize the potential of their surroundings, develop creative economic ideas, and foster awareness of environmental responsibility based on Christian values. Implementation methods included seminars, outreach, and face-to-face interactive discussions, fostering two-way communication between speakers and the community. The high level of community enthusiasm was evident in the level of attendance and active participation in the discussions, which demonstrated a positive response to the material presented and the potential for continued activities in the future.